Baseline assessment of coastal water quality, in Vanuatu, South Pacific: Insights gained from in-situ sampling. (November 2020) - Devlin, Michelle; Smith, Andy; Graves, Carolyn A.; Petus, Caroline; Tracey, Dieter; Maniel, Michael; Hooper, Eryn; Kotra, Krishna; Samie, Erie; Loubser, David; Lyons, Brett P.
Abstract: Nearshore deterioration of water quality in Pacific coastal waters is a growing problem, associated with increasing urban and industrial sewage discharges, and agricultural runoff. Published water quality studies in the Pacific region are limited in both number and scope, making it difficult to resolve the extent of the issue or quantify the variability of water quality across Pacific islands and countries. This study collected water quality measurements over three years in the coastal waters around the Island of Efate (Vanuatu) with majority of work carried out in Port Vila, its capital. Port Vila is the key urban centre for Vanuatu where the increasing population and pollution inputs are placing substantial pressure on the coastal environment. Highest concentrations of dissolved nutrients and suspended sediments were measured adjacent or near the urban drains that enter the coastal areas along the capital's seafront, highlighting many of the issues around anthropogenic inputs are linked to the increasing urbanisation in Port Vila Bay. We provide baseline data that explores variability of coastal water quality and these types of datasets for Pacific islands are a first step towards facilitating development of long-term monitoring programmes and informing coastal zone management decision making. Highlights: Published water quality studies in Pacific are limited in both number and scope This study collected water quality measurements over three years in the coastal waters around the Island of Efate (Vanuatu) Highest concentrations of most water quality parameters were measured adjacent or near the urban drains that enter the coastal areas along the capital's seafront